Estudio de la calidad de los servicios de telefonía móvil (cnt, movistar y claro), en el cantón Bolívar, Manabí - Mendoza Loor, Eddy Gregorio (2019)
This degree work whose subject is called the Study of the quality of mobile telephone services (CNT, Movistar and Claro), in the Canton Bolívar, Manabí, addresses the diagnosis of operators as the first objective, considering the level of satisfaction and perception of the services offered to users through a survey within the Canton, according to the indicators the SCSB Model (Swedish Customer Satisfaction Barometer); On the other hand, the quality parameters involved in the services were identified through an evaluation methodology, which allowed interpreting the data relevant to coverage, call stability, limited availability of services and speed of Internet access; among other characteristics obtained by the monitoring tools (Network Cell Info Lite and Signal Strength, Info-Information of the network signal, OpenSignal, CoberApp, Speedtest), which were applied in real time for their respective comparative analysis; Finally, strategies were established for the improvement of services through a plan, where it is indicated how operators can take actions of solutions and decisions directed towards positive changes in the updating or improvement of telecommunications infrastructures (towers, antennas, equipment and software), and in this way expose their requirements to the company ARCOTEL ZONAL 4 to invest in improved technologies of 2G, 3G, 4G - LTE, HSPA +, UMTS, GSM, especially in areas with greater limitations in service availability, thus giving a 5G oriented progress initiative according to the demand of the society we live in.